Pemanfaatan Tumbuhan Lokal sebagai Representasi Kearifan Budaya dan Sumber Belajar IPA di SMPN 3 Sampit - Luthfia Noorannisa; Selia Selia (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to describe the utilization of local plants as a representation of cultural wisdom and as a learning resource in science education at SMPN 3 Sampit. A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation involving ninth-grade students (class IX, room 7) who participated in the school’s regular healthy breakfast program every Tuesday. The findings revealed that students are familiar with various Dayak local plants, including kelakai (Stenochlaena palustris), pucuk kunjui (Manihot esculenta), sulur keladi (Colocasia esculenta), young rattan (Calamus spp.), and terong asam/rembang (Solanum ferox). However, none of the students brought foods derived from these plants as part of their school meals, primarily because parents consider modern foods more practical, appealing to children, and more appropriate for school. This indicates a gap between students’ knowledge of local biodiversity and its practical application in daily life. The study concludes that integrating ethnobotanical knowledge into science learning—such as through school breakfast activities—can bridge this gap, enabling students to connect science with real-life contexts, appreciate cultural values, and foster awareness of local plant conservation.